97.3k views
0 votes
Mn^3 / m^-3 simplify the given expression completely.. write your answer without negative exponents

User Djzhao
by
4.7k points

1 Answer

3 votes

Answer:

m⁴n³n

Step-by-step explanation:

Given the expression:


(mn^3)/(m^(-3))

We can write the negative exponent as a fraction:


\begin{gathered} mn^3/ m^(-3) \\ =mn^3/(1)/(m^3)\text{ (Change the division to multiplication)} \\ =mn^3* m^3\text{ (Reorder to combine like terms)} \\ =m* m^3* n^3 \\ =m^4* n^3 \\ =m^4n^3 \end{gathered}

The simplified expression is m⁴n³.

User Ameencarpenter
by
4.4k points